Resident TH2 cells orchestrate adipose tissue remodeling at a site adjacent to infection - Kabat, Agnieszka M.; Hackl, Alexandra; Sanin, David E.; Zeis, Patrice; Grzes, Katarzyna M.; Baixauli, Francesc; Kyle, Ryan; Caputa, George; Edwards-Hicks, Joy; Villa, Matteo; Rana, Nisha; Curtis, Jonathan D.; et al. (Science immunology, 2022)
Type 2 immunity is associated with adipose tissue (AT) homeostasis and infection with parasitic helminths, but whether AT participates in immunity to these parasites is unknown. We found that the fat content of mesenteric AT (mAT) declined in mice during infection with a gut-restricted helminth. This was associated with the accumulation of metabolically activated, interleukin-33 (IL-33), thymic stromal lymphopoietin (TSLP), and extracellular matrix (ECM)-producing stromal cells. These cells shared transcriptional features, including the expression of Dpp4 and Pi16, with multipotent progenitor cells (MPC) that have been identified in numerous tissues and are reported to be capable of differentiating into fibroblasts and adipocytes. Concomitantly, mAT became infiltrated with resident T helper 2 (TH2) cells that responded to TSLP and IL-33 by producing stromal cell-stimulating cytokines, including transforming growth factor β1 (TGFβ1) and amphiregulin. These TH2 cells expressed genes previously associated with type 2 innate lymphoid cells (ILC2), including Nmur1, Calca, Klrg1, and Arg1, and persisted in mAT for at least 11 months after anthelmintic drug-mediated clearance of infection. We found that MPC and TH2 cells localized to ECM-rich interstitial spaces that appeared shared between mesenteric lymph node, mAT, and intestine. Stromal cell expression of epidermal growth factor receptor (EGFR), the receptor for amphiregulin, was required for immunity to infection. Our findings point to the importance of MPC and TH2 cell interactions within the interstitium in orchestrating AT remodeling and immunity to an intestinal infection.
CRIS-Team Scopus Importer:2023-03-23